2017
DOI: 10.1111/srt.12362
|View full text |Cite
|
Sign up to set email alerts
|

Skin hydration analysis by experiment and computer simulations and its implications for diapered skin

Abstract: Different diapers/diaper technologies are known to have different profiles in terms of their ability to provide wetness protection, which can result in consumer-noticeable differences in wetness. Simulation results based on published literature using data from a number of different diapers suggest that diapered skin hydrates within ranges considered reversible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…, average of the last three measurements). The decrease of TEWL with time observed in the present study is consistent with the trend observed previously (Elkeeb et al, 2010; Saadatmand et al, 2017). Fig.…”
Section: Resultssupporting
confidence: 93%
“…, average of the last three measurements). The decrease of TEWL with time observed in the present study is consistent with the trend observed previously (Elkeeb et al, 2010; Saadatmand et al, 2017). Fig.…”
Section: Resultssupporting
confidence: 93%
“…It ought to be emphasized that in the literature there are many studies (on subjects from different age and gender groups) addressing post-occlusion water diffusion in human stratum corneum, which were recently summarized by Saadatmand et al 21 and analysed using a numerical skin swelling model 16 with the biexponential approximation for the SC diffusivity ( 1 ) and the GAB sorption isotherm ( 29 ). It was concluded that for describing most of the collected SSWL data, in particular, the value of the GAB parameter k must be reduced similar to earlier microcalorimetry studies of human SC 22 .…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that the developed model assumes the Dirichlet-type boundary conditions ( 5 ) on both sides of the SC membrane. However, when the surface of skin is exposed to moving air, it is known 16 , 21 that the Robin-type boundary condition, which relates the water flux at the skin surface to the difference ( ) with a mass transfer coefficient being dependent on the indoor wind velocity, would be more realistic. In this case, in view of Eq.…”
Section: Resultsmentioning
confidence: 99%
“…These utilities are widely used and applied in different medical areas, such as orthopedics, phlebology, geriatrics, surgery, during hospitalization, or due to immobility. The investigation of microclimatic conditions between different textile materials and the skin is important, since unfavorable microclimatic conditions, especially due to pressure, friction, temperature, and moisture, are known to cause dermal irritations, eczema, and diseases and can lead to erosions or ulcerations demanding wound care …”
Section: Introductionmentioning
confidence: 99%
“…The investigation of microclimatic conditions between different textile materials and the skin is important, since unfavorable microclimatic conditions, especially due to pressure, friction, temperature, and moisture, are known to cause dermal irritations, eczema, and diseases and can lead to erosions or ulcerations demanding wound care. [1][2][3][4][5][6][7] A constant pressure decreases the microcirculation in the skin and can entail damage to the blood vessels, capillaries, and surrounding tissue. This becomes considerably obvious in the case of prostheses.…”
Section: Introductionmentioning
confidence: 99%